Reducing Investment Climate Constraints to Higher Growth : Lao People's Democratic Republic Private Sector and Investment Climate Assessment - World Bank; Asian Development Bank (Washington, DC: World Bank, 2012)
The survey on Lao private sector and investment climate covered 303 firms in six sectors and seven provinces (Vientiane City, Oudomxay, Luang Prabang, Luangnamtha, Xayaboury, Savannakhet, and Champassack). The survey included 246 firms in manufacturing covering wood processing, construction materials, garments, textiles/handicraft, and food and beverage sectors and 57 firms in tourism covering hotels, tour operators, and travel agencies. With the exception of the garment and wood processing sectors, which traditionally have larger firms and more foreign investment, most firms in the sample were domestic small and medium enterprises (SMEs). The survey provided three types of information useful for the Investment Climate Assessment: perceptions of firms operating in Lao PDR regarding the relative importance of investment climate constraints to their businesses; quantitative data on firms' performance and productivity; and comparator country information from their ICAs, for benchmarking Lao PDR's investment climate against regional standards.